Spatio-temporal variability in the demersal fish assemblage on the outer continental shelf of the Great Australian Bight. (5th July 2022) - Nitschke, Joshua; Knuckey, Ian; Koopman, Matt; Hudson, Russell; Huveneers, Charlie; Grammer, Gretchen; Ward, Tim M.
Abstract: We examined spatial and temporal variations in the demersal fish assemblage on the continental shelf of the central Great Australian Bight to understand how the assemblage is affected by both fishing and environmental gradients. Data from the Great Australian Bight Trawl Sector (1988–2018) and fishery-independent trawl surveys (2005–2009, 2011, 2015, 2018) were used for the analyses. The independent survey data were used to analyse trends in overall species composition and abundances, while the commercial fishery data were used to extend the time series for the key commercial species, Deepwater Flathead ( Platycephalus conatus ) and Bight Redfish ( Centroberyx gerrardi ). The demersal fish assemblage was dominated by four commercial species: Deepwater Flathead, Bight Redfish, Ocean Jacket ( Nelusetta ayraud ), and Latchet ( Pterygotrigla polyommata ); and one by-catch species: Wide Stingaree ( Urolophus expansus ). Assemblage composition varied between day/night and along an east-west gradient. Survey abundance and commercial catch-per-unit-effort of several species declined at the end of the time series. Survey abundance was low in 2011, 2015, and 2018 for Bight Redfish and in 2015 and 2018 for Deepwater Flathead. Assemblage composition and catch rates of some species recorded in 2011, 2015, and 2018 were distinct from previous years, but the differences appear to reflect the longer gaps between these surveys and the combined effects of historical fishing pressure and environmental variability. Recent downward trends in the abundance indices of target species, as well as long-term changes in the assemblage, demonstrate the need for continued fishery-independent monitoring. The relative importance of fishing pressure, environmental variability, and other human activities in driving these changes warrant further investigation. Highlights: First synthesis of demersal fishes from commercial and survey trawls of GAB shelf. Fish assemblage changed across temporal scales, with limited spatial variations. Abundance indices of key commercial species declined markedly over time. Changes likely driven by combination of fishing and environmental conditions.